Moisture sorption properties of selected seedboard-approved Philippine variety peanuts - Cervantes, Honeylee Faith C.; Dumelod, Benelyn Domingo (1994., 1994)
The moisture sorption data for selected Seedboard-approved peanut varieties BPI Pn 2, UPL Pn 4, UPL Pn 6,UPL Pn 8, and UPL Pn 10 were determined using the proximity equilibrium cell (PEC) method. From the data, their sorption isotherms were constructed and the monolayer values calculated. All except for UPL Pn 10 showed an abrupt increase in moisture absorption at aw 0.10 to 0.20. Equilibrium moisture content (EMC) values for UPL Pn 10 were generally constant. Computed monolayer values of 0.87 to 1.27% point out that peanuts need to be stored at low relative humidity (RH) to prevent growth of A. flavus. However, storage at such condition may lead to autooxidation of unsaturated fatty acids not to mention additional storage expenditures. No moisture content was noted at 9% which is considered the safest storage moisture content for peanuts (NAPHIRE, 1989), therefore, instability of peanuts at any RH at the test temperature (25-27C) used and at the farm storage conditions is confirmed.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Peanuts